Microbiome and ischemic stroke: A systematic review. - Yee Teng Lee; Nor Ismaliza Mohd Ismail; Loo Keat Wei (PLoS ONE, 2021)
Background Ischemic stroke is one of the non-communicable diseases that contribute to the significant number of deaths worldwide. However, the relationship between microbiome and ischemic stroke remained unknown. Hence, the objective of this study was to perform systematic review on the relationship between human microbiome and ischemic stroke. Methods A systematic review on ischemic stroke was carried out for all articles obtained from databases until 22nd October 2020. Main findings were extracted from all the eligible studies. Results Eighteen eligible studies were included in the systematic review. These studies suggested that aging, inflammation, and different microbial compositions could contribute to ischemic stroke. Phyla Firmicutes and Bacteroidetes also appeared to manipulate post-stroke outcome. The important role of microbiota-derived short-chain fatty acids and trimethylamine N-oxide in ischemic stroke were also highlighted. Conclusions This is the first systematic review that investigates the relationship between microbiome and ischemic stroke. Aging and inflammation contribute to differential microbial compositions and predispose individuals to ischemic stroke.